Comparative study of the efficacy of entomopathogenic fungi, chemicals and botanical pesticides in the management of cotton pests and their natural enemies in Benin - Douro-Kpindou, O.K.; Djegui, D.A.; Maffon, S.; Paraïso, A.; Glitho, I.A.; Tamò, Manuele (2013)
In many African countries, the misuse of chemical insecticides is questioned with the awareness of their negative effects on ecosystems and human health. There is, therefore, constant request from consumers for alternatives to chemical insecticide in plant protection. In the present study, the efficacy of Beauveria bassiana, Metarhizium anisopliae, neem oil and pesticides used for conventional cotton was tested in two environments: (i) experimental plots (Research Centre), (ii) farmers’ cotton field). For the purpose, fifty grams per ha of conidia of each fungus’s strains were formulated with peanut oil and kerosene (30:70) and applied at a volume of 2 litres.ha-1. Neem oil was applied at 1 litre.ha-1 in a formulation containing neem oil and kerosene (50:50). Treatments with biopesticides and neem oil were carried out on threshold (five H. armigera for 40 cotton plants). The effects of the different pesticides used on cotton pests populations’ densities (Helicoverpa armigera, Earias spp., Diparopsis watersi, Spodoptera littoralis, Syllepte derogata) and their natural enemies were studied as well as their damage on cotton buds and bolls. Cotton yield was also assessed. The results showed that, in the experimental plots the average efficacy of pesticides used, calculated on the basis of the observations of Helicoverpapopulation’s density was: 56.1 ± 27.4%; 77.9 ± 9.9%; 59 7 ± 18.6% and 78.21 ± 8.2% for chemical pesticides, neem oil, B. bassiana and M. anisopliae, respectively. The average rate of flowers buds and bolls damaged in plots treated with biopesticides was significantly higher than in plots treated with chemicals. M. anisopliae, B. bassiana and neem oil have protected the fruiting organs in the same manner. In farmers’ cotton fields, pest control by the various pesticides used was similar with yields ranging from 1.5 ± 0.3 t / ha to 1.6 ± 0.3 t / ha. Among the natural enemies observed, ants were the most affected by chemical treatments. Among the biopesticides, M. anisopliae represented the least harmful to natural enemies, followed by B. bassiana. The results showed that the biopesticides used in our study can reduce the densities of different target pests. Early application (at lower threshold) allowed these biopesticides to better control cotton pests.This study suggested the possibilities of the use of biopesticides as alternatives to chemical insecticides in the control of cotton pests.